Family Accounts: A New Paradigm for User Accounts Within the Home Environment - Egelman, Serge; Brush, A.J.; Inkpen, Kori (Conference on Computer supported cooperative work (CSCW 2008), 2008)
In this paper we present Family Accounts, a new user account model for shared home computers. We conducted a study with sixteen families, eight who used individual profiles at home, and eight who shared a single profile. Our results demonstrate that Family Accounts is a good compromise between a single shared profile and individual profiles for each family member. In particular, we observed that because Family Accounts allowed individuals to switch profiles without forcing them to interrupt their tasks, family members tended to switch to their own profiles only when a task required some degree of privacy or personalization.